Isolation and characterization of phosphate solubilizing bacteria naturally colonizing legumes rhizosphere in Morocco - Janati, Walid; Mikou, Karima; El Ghadraoui, Lahsen; Errachidi, Faouzi (Frontiers in Microbiology, 2022)
Low-cost and environmentally friendly agricultural practices have received increasing attention in recent years. Developing microbial inoculants containing phosphate (P) solubilizing bacteria (PSB) represents an emerging biological solution to improve rhizosphere P availability. The present study aims to explore PSB strains isolated from soils located at different bioclimatic stages in Morocco and present in various legumes rhizosphere to improve agronomic microbial fertilizer's effectiveness. In this objective, strains isolated from semi-arid, sub-humid, and humid regions of Morocco were tested for their ability to solubilize P in NBRIP medium with Tricalcium P Ca3(PO4)2 (TCP) alone, rock phosphate (RP) alone and combination of RP and TCP as the only phosphorus source. Bacterial strains with a high P solubility index (PSI) were selected, characterized, and compared to commercial control strains. Vanadate-molybdate method was used to estimate P solubilization activity. In addition, stress tolerance to salinity, acidity, drought, and temperature were tested. From all isolated strains (64), WJEF15 showed the most P solubility efficiency in NBRIP solid medium with PSI = 4.1; while WJEF61 was located as the most efficient strain in NBRIP-TCP liquid medium by releasing 147.62 mg.l-1 of soluble P, in contrast, in the NBRIP-RP medium, strain WJEF15 presented maximum solubilization with 25.16 mg.l-1. Combination of RP and TCP strain WJEF63 was the most efficient with a concentration of (102.69 mg.l-1). Besides, twelve strains were screened as promising biotechnological interest because of their good resistance against different environmental. Indeed, among the selected strains, four strains were able to limit growth of tested fungi. Our results reveals a potential effect of PSBs collection to support legumes as plants growth-promoting rhizobacteria (PGPR).